Identification and characterization of bone/cartilage-associated signatures in common fibrotic skin diseases - Wu, Ting; Jin, Yifan; Chen, Fangqi; Xuan, Xiuyun; Cao, Juanmei; Liang, Yan; Wang, Yuqing; Zhan, Jinshan; Zhao, Mengjie; Huang, Changzheng (Frontiers in Genetics, 2023)
Background: Fibrotic skin diseases are characterized by excessive accumulation of extracellular matrix (ECM) and activation of fibroblasts, leading to a global healthcare burden. However, effective treatments of fibrotic skin diseases remain limited and their pathological mechanisms require further investigation. This study aims to investigate the common biomarkers and therapeutic targets in two major fibrotic skin diseases including keloid and systemic sclerosis (SSc) by bioinformatics analysis. Methods: The keloid dataset (GSE92566) and the SSc dataset (GSE95065) were downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified, followed by functional enrichment analysis using Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). We then constructed protein–protein interaction network (PPI) and identified hub genes. We explored the possibility of further functional enrichment analysis of hub genes on the Metascape, GeneMANIA and Tissue Nexus platform. Networks of transcription factors (TF)-hub genes and miRNAs-hub genes were established by NetworkAnalyst. We fixed GSE90051 and GSE76855 as the external validation datasets. Candidate hub gene validation used Student’ t-test and ROC curve. Hub gene expression was assessed in vitro by quantitative real-time PCR. Results: A total of 157 overlapping DEGs (ODEGs) were retrieved from the GSE92566 and the GSE95065 datasets, and 5 hub genes (COL11A1, COL5A2, ASPN, COL10A1 and COMP) were identified and validated. Functional studies revealed that hub genes were predominantly enriched on bone/cartilage-related and collagen-related processes. FOXC1 and miR-335-5p were predicted to be master regulators for both transcriptional and post‐transcriptional levels. Conclusions: COL11A1, COL5A2, ASPN, COL10A1 and COMP may help us understand the pathological mechanism of the major fibrotic skin diseases; moreover, FOXC1 and miR-355-5p could build a regulatory network in keloid and SSc.